ArtProtect: Blockchain and NFC‐based anti‐counterfeit system for physical art - Cindy Handoko Tantowibowo; Wei‐Chuen Yau (IET Blockchain)
Abstract Counterfeit artwork presents a significant risk to copyright holders and the economy. Without expertise in art, it is not straightforward to distinguish an artwork counterfeit from a genuine piece. This work designs and implements a reliable solution that enables users with near‐field communication‐enabled Android smartphones to verify artwork authenticity by accessing its respective certificate of authenticity stored in the Ethereum blockchain. To represent a physical artwork, the artwork image and metadata are stored in an inter‐planetary file system and minted as an ERC721 non‐fungible token to a smart contract deployed in Ethereum Rinkeby Testnet. The mobile app ArtProtect was developed to generate certificate of authenticity based on each non‐fungible token fetched through OpenSea Testnet API. Users access this information by scanning an near‐field communication tag embedded into the artwork. The content of the tag is signed by the respective artwork's artist and responsible agent by using Ethereum signing with their Ethereum wallet accounts. Through testing and analysis, the implemented work is secure, tamper‐evident, usable, flexible, and inexpensive to be applied to a real‐world scenario.